Jasmonic acid‐inducible TSA1 facilitates ER body formation. (20th November 2018) - Geem, Kyoung Rok; Kim, Dae Heon; Lee, Dong Wook; Kwon, Yun; Lee, Junho; Kim, Jeong Hee; Hwang, Inhwan
Summary: Members of the Brassicales contain an organelle, the endoplasmic reticulum (ER) body, which is derived from the ER. Recent studies have shed light on the biogenesis of the ER body and its physiological role in plants. However, formation of the ER body and its physiological role are not fully understood. Here, we investigated the physiological role of TSK‐associating protein 1 (TSA1), a close homolog of NAI2 that is involved in ER body formation, and provide evidence that it is involved in ER body biogenesis under wound‐related stress conditions. TSA1 is N‐glycosylated and localizes to the ER body as a luminal protein. TSA1 was highly induced by the plant hormone, methyl jasmonate (MeJA). Ectopic expression of TSA1:GFP induced ER body formation in root tissues of transgenic Arabidopsis thaliana and in leaf tissues of Nicotiana benthamiana . TSA1 and NAI2 formed a heterocomplex and showed an additive effect on ER body formation in N. benthamiana . MeJA treatment induced ER body formation in leaf tissues of nai2 and tsa1 plants, but not nai2/tsa1 double‐mutant plants. However, constitutive ER body formation was altered in young seedlings of nai2 plants but not tsa1 plants. Based on these results, we propose that TSA1 plays a critical role in MeJA‐induced ER body formation in plants. Significance Statement: We identified TSA1 as a critical factor for MeJA‐induced ER body formation.